Hubungan Keanekaragaman dan Keberadaan Plankton Terhadap Faktor Fisika Kimia Sungai Batanghari - Marhadi Marhadi; Ira Galih Prabasari; Ria Pratiwi (Jurnal Daur Lingkungan, 2018)
Water pollution can not only be measured only by chemical and physical parameters, Plankton have properties that are always moving so that they can be used as indicators of water pollution. Plankton play an important role in influencing the primary productivity of river waters. The purpose of this study was to determine the relationship between the diversity and presence of plankton to the quality of the Batanghari River. The study was conducted in February 2018 in Jambi City. Primary data taken in the form of concentrations of physical and chemical parameters include turbidity, pH, TDS, BOD, COD, DO, Phosphate, Nitrate, Nitrite, Ammonia, Lead, Chloride, Sulfate and the amount of plankton abundance (ind / L) on the Batanghari River. The time of sampling was in the morning and evening on the same day.  The results showed that the relationship between the existence of plankton and the quality of the Batanghari River showed the condition of the Batanghari River in Jambi City was in phase a - Mesosaprobic (heavy pollutant level). Parameters of pH, COD, Phosphate, Nitrite, Lead and Chloride are moderately correlated to phytoplankton, while TDS, BOD, DO, Nitrate and Ammonia are weakly correlated with phytoplankton. And for temperature parameters it is strongly correlated with phytoplankton. For correlation to zooplankton, parameters of pH, TDS, BOD, COD, COD, DO, Phosphate, Nitrate, Nitrite, Lead, chloride are very weakly correlated while ammonia and turbidity correlate moderately to zooplankton.